(untitled) (Proceeding of the International Conference on Arts and Humanities, 2021)
Photoshop CC (Creative Cloud) is software that is becoming prevalent among university students especially in the field of art and photography. It is an amazing tool that allows people to bring out their creativity in editing photos, creating websites, advertisement, newsletters and many more. In mastering how to use the software, tutorial videos can be one of the best methods for learning purposes. The purpose of this paper is to analyse students’ perception by using Photoshop CC tutorial videos in YouTube for the first-time users. The methodology used in this paper is quantitative and qualitative. Total samples of 50 questionnaires were collected using an online channel, involving undergraduate university students. Results showed that learning Photoshop CC using tutorial videos in YouTube can be effectively due its accessibility with Internet access and gadgets. Majority of the respondents agreed that videos which are too long might hinder the learning process because of the attention span of the viewers. Additionally, most of them also agreed that tutorials videos in Malay language are still less available online. Therefore, it been suggested that videos should be done in short duration and provide other languages including Malay as well.